+0  
 
0
112
2
avatar+56 

Solve the following equation: \(log_3(x+3)+log_3(x-5)=2\)

 May 9, 2021
 #1
avatar+34430 
+3

x=6

 

Log3 ((x+3)(x-5) ) = 2

log3 (x^2-2x-15) = 2

x^2 - 2x - 15 = 3^2

x^2 -2x-24 =0

(x-6)(x+4) = 0      x = 6    or   -4 (throw out....cannot have log of a negative )

 May 9, 2021
 #2
avatar+56 
+1

Oh it makes sense now! I only had issues when it came to the part when there was the 3^2, so I must've forgotten a log rule there. 

stressedmathkid123  May 9, 2021

34 Online Users

avatar